Optimalisasi Pemanfaatan Energi Surya untuk Kemandirian Energi Rumah Tangga di Wilayah Pesisir Desa Jetis Kecamatan Nusawungu Kabupaten Cilacap: Pengabdian - Susatyo Adhi Pramono; Endang Sri Wahyuningsih; Isra’ Nuur Darmawan; Dadi Tri Awan Selalatu; Irawan Dharma Sukowati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service program aims to optimize the use of renewable energy through the development of household-scale Solar Power Plants (PLTS) in Jetis Village, Nusawungu District, Cilacap Regency. The initiative is motivated by the limited access to stable electrici7. The implementation method adopts a participatory approach that directly involves the local community in every stage—from identifying energy needs, providing technical training, and installing the solar power system, to establishing a local energy management institution. The results show that the implementation of a PLTS system with a capacity of 450–500 Wp can meet up to 75–85% of household electricity needs and reduce electricity expenses by 35–40%. In addition, there was an increase in the community’s knowledge and awareness of clean energy, indicated by a 37% average improvement in energy literacy scores after the training. Socially, the formation of the Papringan Village Energy Group serves to ensure the sustainability of the system and strengthen community solidarity in energy management. The program also positively impacts local economic activities, particularly small household businesses in seafood processing and culinary sectors.